Perancangan Aplikasi Mobile Kalkulator Pakan Ikan Berbasis Android untuk Optimalisasi Formulasi Pakan - Prasetyo, Rian; Komariah, Ainur (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Feed is a main factor influencing fish growth. However, feed formulation using traditional methods such as the Pearson Square is often considered complex and time-consuming for fish farmers. This study aims to design and development an Android-based application named “Hitung Pakan”, which can calculate fish feed formulations quickly and accurately. The research employed the waterfall method, including requirement analysis, system design, implementation, and testing. The application was developed using Java programming language and tested by 10 respondents from a fish farming group. The results showed no differences between the application’s calculations and manual calculations using Pearson Square method equations. This indicates that the developed application provides accurately results, simplifies the formulation process, and reduces human error. Therefore, the application is feasible to be used as a formulation tool in fish farming group.Keywords - Android Application, Calculation Efficiency, Fish Feed Formulation, Pearson Square.